Monitoring Tegangan, Arus, dan Daya Pada PLTS 20WP Berbasis Internet of Things (IoT) - Syamsudin, Mariana; Ilyas Hadikusuma, Mohd; Deyi, Deyi; Satriyo, Satriyo; Rianda, Rianda (Electrical Network Systems and Sources, 2024)
Solar Power Plants (PLTS) have great potential in Indonesia due to the year-round sunshine. To monitor the performance of solar panels, which are the main component of PLTS, an effective monitoring system is required. However, there are several challenges in remote monitoring of PLTS. The solution is to use a device that helps humans monitor PLTS performance and send notifications to phones or computers via the internet. One platform that can be used is Adafruit, an IoT platform that offers remote monitoring via the internet with hardware support and a broad community. The obtained data show that the measurement values of current, voltage, and power from the battery, solar panels, and inverter have relatively small deviations, with a Relative Deviation Average (RSR) of 4.4676%. The Overall Accuracy Rate, reaching 95.5324%, indicates that the system is reliable in providing accurate measurements, closely matching the expected reference values. Keywords: Monitoring System, Internet of Things (IoT), Adafruit.